231k views
5 votes
I need help on factoring and making it equal to zero

I need help on factoring and making it equal to zero-example-1

1 Answer

4 votes

Since the given function is


f(x)=7x^4-17x^2-12

Take 7 as a common factor


f(x)=7(x^4-(17)/(7)x^2-(12)/(7))

Now let us make the trinomial completing square

Divide the middle term by 2, then square it


\begin{gathered} ((17)/(7))/(2)x=(17)/(14) \\ ((17)/(14))^2=(289)/(196) \end{gathered}

So we will add and subtract this value


\begin{gathered} x^4-(17)/(7)x-12=x^4-(17)/(7)x^2+(289)/(196)-(289)/(196)-12 \\ =(x^4-(17)/(7)x^2+(289)/(196))-(2641)/(196) \end{gathered}

The trinomial is the square of


(x^4-(17)/(7)x^2+(289)/(196))=(x^2-(17)/(14))^2

Then the new f(x) is


f(x)=7\lbrack(x^2-(17)/(14))^2-(2641)/(196)\rbrack

Now we can solve it by equating f(x) by 0


\begin{gathered} f(x)=0 \\ 7\lbrack(x^2-(17)/(14))^2-(2641)/(196)\rbrack=0 \end{gathered}

Divide both sides by 7 and add 2641/196 to both sides


\begin{gathered} (x^2-(17)/(14))^2-(2641)/(196)+(2641)/(196)=0+(2641)/(196) \\ (x^2-(17)/(14))^2=(2641)/(196) \end{gathered}

Take a square root to both sides


(x^2-(17)/(14))=\pm\sqrt[]{(2641)/(196)}

Add 17/14 to both sides


\begin{gathered} x^2-(17)/(14)+(17)/(14)=\pm\sqrt[]{(2641)/(196)}+(17)/(14) \\ x^2=\pm4.885047188 \end{gathered}

We will cancel the -ve value because no square root of -ve values, then

Take a square root for 4.885047188 to find x


\begin{gathered} x=\pm\sqrt[]{4.885047188} \\ x=\pm2.210214286 \end{gathered}

User Hanmant
by
4.5k points